ISU PELAKSANAAN AKTA SEKATAN DALAM KEHIDUPAN DEMOKRASI DI MALAYSIA - Feri Fadli Rizki Feri Fadli Rizki (NIAGARA Scientific Journal, 2016)
This paper just to remind, that the Acts of repression still valid in Malaysian democratic life, although the Acts is always met with resistance from opposition groups , NGOs , students and independent groups, but the Malaysian Government to enforce the Acts of the grounds , that the decision was made to maintain the stability and peace of the country. The implementation of the Acts is also used to arrest the demonstrators, NGO and student activists, democracy activists, opposition party activist who fought against the policy of the Government. Source analysis of this paper consists than official reports (Malaysian Bureau of Democracy, Human Rights and Labor Malaysia), books and articles in scientific journals, online media, and the author's observation to political developments in Malaysia. This paper can provide some measure of information or a description of the implementation of the Acts of repression by the Malaysian Government that is always met with resistance from the power of oppositions in Malaysia.